Complete remission in a pretreated, microsatellite-stable, KRAS-mutated colon cancer patient after treatment with sintilimab and bevacizumab and platinum-based chemotherapy: a case report and literature review - He, Lijuan; Li, Haiyuan; Wang, Yunpeng; Li, Weidong; Gao, Lei; Xu, Bo; Hu, Jike; He, Puyi; Pu, Weigao; Sun, Guodong; Wang, Zhuanfang; Han, Qinying; et al. (Frontiers in Immunology, 2024)
Postoperative recurrence and metastasis of colon cancer remains an incurable disease, and it is difficult for existing treatments to achieve desired clinical outcome, especially for colon cancer patients who have received first-line treatment. Immune checkpoints inhibitors (ICIs) have demonstrated durable clinical benefit in many solid tumors involving colon cancer. Inflamed tumors like microsatellite instable (MSI) colon cancer respond well to ICIs, whereas ICIs have poor clinical efficacy in patients with microsatellite stable (MSS) colon cancers. Although combination therapies have shown its advantage even for MSS-type colon cancer, it remains unclear whether combination therapies show their advantage in patients with postoperative recurrent metastatic colon cancer. We report a patient who has achieved complete remission and good tolerance with sintilimab plus 2 bevacizumab and platinum-based chemotherapy after postoperative recurrence. The patient was KRAS mutated, microsatellite stable (MSS), while PD1+CD8+ positive, CD3-CD19-CD14 +CD16-HLA-DR positive. Progression-free survival for this patient was 43 months and overall survival was 52 months up to now, follow up at our center. Consequently, the combination therapy produces longterm response in pretreated, MSS-type, and KRAS mutated recurrent and metastatic colon cancer.